Effects of NaCl concentration, electrolysis time, and electric potential on efficiency of electrolyzed oxidizing water on the mortality of Penicillium digitatum in suspension - K. Whangchai (2018)
This research investigated factors (salt concentration, electrolysis time, and electric potential) which affected the electrolysis efficiency of electrolyzed oxidizing (EO) water on mortality of Penicillium digitatum cells in suspension. An electrolysis time of 60 min, with electric potential (8 V), and 5% w/v NaCl solution produced the highest efficiency of EO water. Electrolysis efficiency, represented by available free chlorine, varied up to 385 ppm. The pH varied between 2.6 and 3.2, electrical conductivity varied from 30-48 mS/cm, and ORP (Oxidation Reduction Potential) was 250 mV. In vitro tests determined the inhibitory effect of EO water on the growth of P. digitatum when incubated at 28 °C for 48 h.